1992
DOI: 10.1073/pnas.89.21.10306
|View full text |Cite
|
Sign up to set email alerts
|

Activation of human peripheral blood T lymphocytes by pharmacological induction of protein-tyrosine phosphorylation.

Abstract: Protein-tyrosine kinase and protein-tyrosine phosphatase (PTPase) activities are essential for T-cell antigen receptor-mediated signalng. To assess the functional consequences of alteration of the levels of tyrosine phosphorylation in normal human T cells, the effects of vanadate and hydrogen peroxide were studied. In combination, these agents induced tyrosine phosphorylation of cellular substrates, elevated cytosolic free calcium, and induced interleukin 2 receptor (IL-2R) a chain expression but not IL-2 secr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
106
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(110 citation statements)
references
References 41 publications
4
106
0
Order By: Relevance
“…It has been known for more than a decade that tyrosine phosphatase activity is associated with a negative regulatory effect on T cell function. Thus, early experiments showed that generalized phosphatase inhibition results in persistent proliferation of polyclonally activated T cells (15) or can induce spontaneous activation and cytokine release by resting T cells (16). A specific role of PTPN22 in T cell regulation has been confirmed by the results of knocking out the murine homolog of PTPN22 (PEST domainenriched tyrosine phosphatase [PEP]), resulting in lowered thresholds for T cell receptor signaling in these animals (17).…”
Section: Peter K Gregersen and Franak Batliwallamentioning
confidence: 99%
“…It has been known for more than a decade that tyrosine phosphatase activity is associated with a negative regulatory effect on T cell function. Thus, early experiments showed that generalized phosphatase inhibition results in persistent proliferation of polyclonally activated T cells (15) or can induce spontaneous activation and cytokine release by resting T cells (16). A specific role of PTPN22 in T cell regulation has been confirmed by the results of knocking out the murine homolog of PTPN22 (PEST domainenriched tyrosine phosphatase [PEP]), resulting in lowered thresholds for T cell receptor signaling in these animals (17).…”
Section: Peter K Gregersen and Franak Batliwallamentioning
confidence: 99%
“…Since the mechanisms regulating tyrosine phosphorylation of Bgp have not been clearly de®ned, we chose to arti®cially induce Tyr phosphorylation by treatment with pervanadate, a potent inhibitor of cellular protein tyrosine phosphatases (O'Shea et al, 1992). This choice was based on the observation of others, which showed that vanadate, a less active protein tyrosine phosphatase inhibitor was e cient at provoking phosphorylation of Bgp at Tyr 488 .…”
Section: Tyrosine Phosphorylation Of Bgp In Pervanadate-treated Colonmentioning
confidence: 99%
“…All experiments were performed with a minimum of two clones for each transfectant cell line. Pervanadate treatment of cells was performed by incubating CT51 transfectant cells in a-minimal essential medium for 10 min at 378C with a 10 mM H 2 O 2 and 100 mM sodium vanadate solution (O'Shea et al, 1992). Cells were collected from the dishes by scraping followed by centrifugation (1500 r.p.m.)…”
Section: Cell Culturementioning
confidence: 99%
“…Experiments were performed with either cell populations or a minimum of two clones for each transfectant cell line. Pervanadate treatment of cells was performed by incubating transfected CT51 cells in ␣-minimal essential medium for 10 min at 37°C with a solution of 10 mM H 2 O 2 and 100 M sodium vanadate (38). Cells were collected from the dishes by scraping, followed by centrifugation and subsequent washes in the same vanadate-containing medium.…”
Section: Methodsmentioning
confidence: 99%